Seasonality and sustainability of tourism - Pavlović, Sanja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2022)
The role of seasonality in the sustainability of tourism is multiple and complex. The connection between seasonality and sustainability is even more complex when it comes to protected areas. This connection was investigated on the examples of selected protected mountain areas in Serbia ? Kopaonik and Tara National Parks, and Stara planina and Zlatibor Nature Parks. The Gini index was used to measure seasonality, and to show the imbalance in the monthly distribution of the number of tourist overnight stays in the mentioned destinations, in the period 2013?2021. The research results show that the analyzed protected mountain areas in Serbia have different values of the Gini index, which is conditioned by their natural predispositions for tourism development (e.g. altitude and duration of snow cover), and at the same time the levels of tourist development of the area. In order to reduce the effects of seasonality, in each of the destinations that are the subject of this paper, alternative types of tourism and activities are implemented.
Keywords: environmental protection; geography of tourism; protected areas; Serbia; Srbija; sustainable development; trajnostni turizem; turizem; varstvo okolja; zavarovana območja